Can culture explain economic growth? A note on the issues regarding culture-growth studies - Uy, Arnel Onesimo O. (Animo Repository, 2009)
The notion that culture affects economic develop and therefore explains growth has pre-occupied social scientists for decades. Studies have shown mixed results, some supporting that economic growth is shaped (at least in part) by cultural factors while others conclude otherwise. Intuitively, culture should affect growth since culture defines the belief systems of the people making up the economy and thus would ultimately affect economic growth. But the question is how do we show that empirically? This paper attempts to answer that question by reviewing literature and examining more recent studies on the culture-growth dilemma then proceeds with summarizing issues regarding such studies as how they can possibly be resolved.